Retransplantation in a patient with cystic fibrosis. Issue 11 (1st November 1998) - McCloskey, M; Maxwell, A P; Hall, V; Redmond, A O B; Elborn, J S
Abstract : A patient with cystic fibrosis is described who requested a third lung transplant. The medical and ethical issues involved are discussed.